Thermal-Treatment-Induced Enhancement in Effective Surface Area of Single-Walled Carbon Nanohorns for Supercapacitor Application - Jung, Hwan Jung; Kim, Yong-Jung; Han, Jong Hun; Yudasaka, Masako; Iijima, Sumio; Kanoh, Hirofumi; Kim, Yoong Ahm; Kaneko, Katsumi; Yang, Cheol-Min (American Chemical Society, 2013)
We investigated the importance of the specific effective surface area through a detailed study on the relationship between electrical conductivity of single-walled carbon nanohorns (SWCNHs) and accessibility of the electrolyte ions in the SWCNH-based supercapacitor. After heat treatment of the SWCNHs, the ratio of sp(2)/sp(3) carbons dramatically increased, suggesting an enhanced electrical conductivity of the SWCNHs. Even though the specific surface area (SSA) slightly decreased by 16% as a result of heat treatment, the specific capacitance per SSA of the SWCNH electrode remarkably increased from 22 to 47 mu F cm(-2). Such a result indicates an explicit increase in accessible effective surface area by electrolyte ions. Our result clearly showed that a higher degree of utilization for the interstitial pore of SWCNHs by solvated ions is a key factor in achieving a high volumetric capacitance of SWCNH-based supercapacitors.
Keywords: CAPACITANCE; PORE; ADSORPTION; SIMULATION; NANOTUBES; ELECTRODE; SIZE